An effective Physical Developer (PD) method for use in Australian laboratories. Issue 6 (2nd November 2018) - de la Hunty, Mackenzie; Moret, Sébastien; Chadwick, Scott; Lennard, Chris; Spindler, Xanthe; Roux, Claude
ABSTRACT : Physical Developer (PD) is an underutilized technique for the development of latent marks on porous surfaces that have been wet, or as a subsequent technique in a development sequence. It is a multistep technique that works by selectively reducing silver ions to silver metal at nucleating sites in fingermark residue. Its use is associated with a plethora of issues, largely surrounding the inherent instability of the working solution. Recently, one of the components of the working solution, Synperonic N, has ceased production, and the recommended replacement is Tween 20. This article addresses factors during PD processing using Tween 20, other than reagent formulations that should be considered when using the technique.